Exploration of Risk Oriented Fund Performance Audit—Take Rural Endowment Insurance as an Example - Ronggang Zhang; Lanzhihao Liu (Journal of Risk Analysis and Crisis Response (JRACR), 2019)
The performance audit risk of rural pension fund is worth studying deeply. Based on the cost-benefit principle and the public fiduciary economic responsibility theory, this paper analyzes the current situation and causes of the performance audit of rural pension fund and finds that the audit demand degree is not enough. This paper proposes to integrate risk orientation into performance audit and adopt different audit methods and evaluation systems to improve audit efficiency and reduce costs by dividing risk levels and optimizing performance audit.